2020
DOI: 10.1038/s41598-020-74294-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of interactions between white sharks and large squids in Guadalupe Island, Mexico

Abstract: Shark-cephalopod interactions have been documented in trophic ecology studies around the world. However, there is little information about the encounters between white sharks Carcharodon carcharias and squids in the eastern North Pacific Ocean. Here we provide evidence of interactions between white sharks and large squids in the waters of Guadalupe Island, Mexico. Through the use of non-invasive techniques, we found the presence of evident scars made by large squids on the body of the white sharks, mainly on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Thus, our results do not provide support for an effect of habitat use or thermal tolerance on foraging depth, and subsequent MeHg exposure, for white sharks over 2 m in total length. Alternatively, both juveniles and adult sharks could have access to the same mesopelagic prey that migrate to the surface at night, such as large squids, facilitated by the very steep bathymetry and oceanic nature of Guadalupe Island. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our results do not provide support for an effect of habitat use or thermal tolerance on foraging depth, and subsequent MeHg exposure, for white sharks over 2 m in total length. Alternatively, both juveniles and adult sharks could have access to the same mesopelagic prey that migrate to the surface at night, such as large squids, facilitated by the very steep bathymetry and oceanic nature of Guadalupe Island. , …”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, both juveniles and adult sharks could have access to the same mesopelagic prey that migrate to the surface at night, such as large squids, facilitated by the very steep bathymetry and oceanic nature of Guadalupe Island. 89,101 During the seasonal offshore migration, Northeast Pacific white sharks occupy a pelagic zone referred to as the "White Shark Cafe", also known as the "Shared Offshore Foraging Area" (SOFA), located in the North Pacific Subtropical Gyre halfway between Hawaii and the coasts of Mexico. 19,24,99 The reason why a large number of white sharks congregate in this area remains unanswered, and the two main hypotheses proposed relate to reproduction or feeding.…”
Section: T H Imentioning
confidence: 99%
“…While the role of the island for this white shark population is unclear, evidence in previous studies showed that it can serve as a secondary nursery area for juveniles and as a feeding area for adults, which benefit from the pinniped colonies (mainly the northern elephant seal), although the frequency of attacks on them (seen at the surface) is not as high as in other areas such as California, which could be due to the excellent water clarity that allows ambush in deep waters (Domeier et al, 2012;Hoyos-Padilla et al, 2016;Skomal et al, 2015). Moreover, according to new evidence (Becerril-García et al, 2020;Le Croizier et al, 2020;Papastamatiou et al, 2020), Guadalupe Island could be more important than previously thought in terms of access to mesopelagic prey, acting as a barrier trap and hindering their dispersion.…”
Section: Unlike Many Other White Shark Aggregation Sites Guadalupementioning
confidence: 99%
“…This increase in YOY and juveniles was also reflected in the behaviours recorded in this study. According to Given that Guadalupe Island is of volcanic origin with a rapidly descending shelf, the preferred habitat for juveniles is limited to this narrow coastal strip (Castro et al, 2005;García-Gutiérrez et al, 2005;Becerril-García et al, 2020a), which represents a critical habitat for juvenile white sharks due to the protection offered from adult sharks and the overlapping distributions of forage species around the island (Hoyos-Padilla et al, 2016;Becerril-García et al, 2020a). Similar findings and juvenile foraging patterns have been reported along the coasts of the southern California Bight and Vizcaino Bay (Santana-Morales et al, 2012;Oñate-González et al, 2017;White et al, 2019;Santana-Morales et al, 2020).…”
Section: Observed Behavioursmentioning
confidence: 99%